Four women at the top: The self-image and media representation of female leaders in Soviet and Post-Soviet Estonian architecture - Ruudi, Ingrid (2022)
Focusing on four case studies of high-ranking Estonian architects, the article analyses the career goals and possibilities for advancement of women in design in the Soviet and the post-Soviet periods. Based on in-depth interviews and representation in mainstream and professional media, the article compares and juxtaposes the architects’ public personas and self-perception as revealed in the interviews, highlighting the conditions of self-realization, organizational and design goals, networks of support and balancing the demands of high-profile design and managerial jobs with personal and family responsibilities. The cases reveal a complicated and ambivalent relationship to feminist agenda and the local specificities of the problem, delineating its possible causes from the Soviet to the post-Soviet period, and at the same time pointing towards the changes that have occurred with the transition from the socialist to the democratic state.